Analysis of The Role Based on The Customary Criminal Justice System of Dayak Bangkalaan in The National Criminal Justice System - Pone, Darlian; Saptomo, Ade; Baharudin, Baharudin; Harahap, Aminuddin; Rustam, Rustam (Syntax Corporation, 2024)
This research is motivated by indigenous peoples' belief in customary rules which encourages studies on their legitimacy in the Indonesian legal system. The author collected study samples from the Bangkalan Dayak tribe in South Kalimantan Province as an example of an Indonesian customary village. This study focuses on two formulations of problems, namely the role of the customary criminal justice system in the national criminal justice system and the impact of Dayak Bangkalan customary criminal justice law enforcement when related to the national criminal justice system. This research is a sociological legal research, the legal data collection technique is carried out through literature review, including primary legal data, secondary legal data, and tertiary legal data related to this research. The result of the study is that the state recognizes the existence of customary law communities in accordance with Article 18B of the 1945 Constitution of the Republic of Indonesia. Even though there is no legal framework that can regulate this at the national level, the mandate of regional legislative policy still recognizes the existence of customary courts. This is evidenced by the existence of regional regulations that recognize and protect indigenous peoples. In addition, the results of the study conveyed that the legal implications arising from customary court decisions turned out to be able to be used as legal data in national criminal courts.